Agrilink- a Web-based Platform Connecting Farmers to Buyers - Emmanuel Vangamoi (Uganda Christian University, 2025)
Smallholder farmers and buyers in agricultural markets often face a disconnect, with farmers losing profits to intermediaries and buyers struggling to find suitable products. This report presents AgriLink: A Web-Based Platform Connecting Farmers to Buyers, crafted by our team to revolutionize this dynamic. AgriLink is a digital bridge that not only links farmers and buyers directly but also leverages machine learning (ML) to deliver personalized recommendations matching farmers with interested buyers and suggesting products to buyers based on their preferences Built with cutting-edge web technologies, AgriLink offers a user-friendly dashboard featuring real-time sales trends, competitor pricing comparisons, and buyer engagement insights. Its standout AI/ML engine analyzes transaction data and behavior to recommend high-potential buyers to farmers and tailored products to buyers, enhancing trade efficiency. A smart-matching system further ensures pricing clarity by grouping similar product names, like ‘Maize’ and ‘Corn.’ Our collaborative approach fused data integration, algorithmic innovation, and user-centric design. AgriLink empowers farmers to bypass middlemen, optimize pricing, and grow sales, while buyers discover relevant offerings effortlessly. This platform redefines agricultural connectivity blending technology and intelligence to uplift rural livelihoods and market vitality.